Clear up mathematic

Power of Powers: Simplifying Exponential Expressions

Simplify: Step 1: Use the division of exponents rule, and subtract the exponents in the denominator from the exponents in the numerator. Step 2: Move negative exponents in the
Solve mathematic Determine mathematic question Math expert

Simplify by Using the Product, Quotient, and Power Rules

We have three basic rules for combining exponents: an · am = an+m \small { \dfrac {a^n} {a^m} = a^ {n-m} } aman =an−m ( an) m = anm However, when simplifying expressions containing
`